Measurement method, evaluation method and measurement device

An on-site method and device for stainless steel using an electrolytic solution with pH 15 to 16 measure anode polarization to detect Cr carbides and nitrides, addressing the limitations of conventional methods by providing accurate corrosion resistance evaluation.

JP2024179650APending Publication Date: 2024-12-26FUJI ELECTRIC CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023098656
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-15
Publication Date
2024-12-26

AI Technical Summary

Technical Problem

Conventional methods for evaluating the corrosiveness of stainless steel welds are time-consuming, require off-site sampling, and lack accuracy in detecting Cr carbides and Cr nitrides, which cause sensitization and reduce corrosion resistance.

Method used

An on-site measurement method using an electrolytic solution with pH 15 to 16 to measure the anode polarization curve of stainless steel, allowing detection of Cr carbides and Cr nitrides by analyzing the charge due to their dissolution, and a measuring device comprising an electrolytic cell, potentiostat, and data recording device to quantify the charge.

Benefits of technology

Enables accurate, on-site evaluation of corrosiveness by detecting Cr carbides and nitrides, preventing mechanical strength loss and ensuring high precision in assessing corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024179650000001
    Figure 2024179650000001
  • Figure 2024179650000002
    Figure 2024179650000002
Patent Text Reader

Abstract

To provide a measurement method which can perform on-site measurement and can evaluate corrosiveness with high accuracy.SOLUTION: A measurement method includes the steps of: bringing stainless steel into contact with an electrolyte solution with pH of 15-16; measuring the anode polarization curve of the stainless steel; and measuring a charge amount caused by the dissolution to the electrolyte solution of chromium carbides and / or chromium nitrides from the anode polarization curve.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a measurement method, an evaluation method, and a measurement apparatus. [Background technology]

[0002] Stainless steel has excellent corrosion resistance and strength, and is used in a variety of applications, including exhaust gas purification equipment. Stainless steel has excellent corrosion resistance due to the formation of a passive film on its surface, which is mainly made of chromium (Cr).

[0003] Stainless steels are sometimes welded in the process of manufacturing structures, but it is known that sensitization (a phenomenon in which Cr carbides and Cr nitrides precipitate in the steel, causing a deficiency of Cr in the vicinity and reducing corrosion resistance) can occur depending on the heat input conditions during welding. When sensitization occurs, the Cr passive film that should normally form does not form, and there is a risk of fatal corrosion or stress corrosion cracking.

[0004] There have been conventional methods for observing such welds in stainless steel. For example, Patent Document 1 discloses that a pitting corrosion test piece is taken from the steel base material near the weld heat-affected zone and the weld metal of a welded structure including a duplex stainless steel base material and a weld including a weld metal and a heat-affected zone, and the pitting corrosion potential is measured in a 3.5% NaCl solution at 50°C in accordance with the method specified in JIS G0577. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent Publication No. 2021-178953 [Patent Document 2] Patent Publication No. 2021-181559 Summary of the Invention [Problem to be solved by the invention]

[0006] However, conventional methods cannot measure on-site and require time-consuming observations. In addition, conventional methods do not check for Cr carbides and Cr nitrides that cause sensitization, so the accuracy of corrosiveness evaluation is low.

[0007] An object of the present invention is to provide a measurement method that enables on-site measurement and enables corrosivity to be evaluated with high accuracy. [Means for solving the problem]

[0008] One aspect of the present invention is a measurement method comprising contacting a stainless steel with an electrolyte having a pH of 15 to 16, measuring an anodic polarization curve of the stainless steel, and measuring the amount of charge due to dissolution of chromium carbide and / or Cr nitride into the electrolyte from the anodic polarization curve. Effect of the Invention

[0009] According to the present invention, there is provided a measurement method which enables on-site measurement and enables corrosivity to be evaluated with high accuracy. [Brief description of the drawings]

[0010] [Figure 1] 1 is a graph showing a potential-current density curve. [Diagram 2] FIG. 1 is a diagram illustrating a measurement device according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present invention will be described with reference to the drawings as appropriate.

[0012] <Measurement method> In the measurement method of the present embodiment, the stainless steel is brought into contact with an electrolytic solution having a pH of 15-16.

[0013] In this specification, stainless steel is a general term for alloy steels that contain iron as the main component, approximately 2% or less of carbon (C), and approximately 10% or more of chromium (Cr). There are no particular limitations on the type of stainless steel, and it may be any of austenitic stainless steel, austenitic-ferritic (duplex), ferritic, and martensitic. Among these, austenitic-ferritic stainless steel (duplex stainless steel) is preferably used.

[0014] Furthermore, the part of the stainless steel that comes into contact with the electrolyte may be a welded part of the stainless steel. Here, the welded part refers to a part including the weld metal and the heat-affected zone. Furthermore, the welded part of the stainless steel is not limited to a welded part that is a part of a single piece of stainless steel, and may be a welded joint in which stainless steel pieces are joined together by welding.

[0015] The electrolyte refers to an electrically conductive solution in which an ionic substance (electrolyte) is dissolved in a polar solvent such as water. The electrolyte having a pH of 15 to 16 is not particularly limited, but examples thereof include aqueous solutions of hydroxides of sodium, potassium, etc. (NaOH, KOH), hydroxides of calcium, barium, etc. (Ca(OH)2, Ba(OH)2), etc. Among these, a saturated aqueous solution of potassium hydroxide (KOH) is preferred because it is easy to adjust the pH to 15 to 16.

[0016] "Contacting the stainless steel with the electrolyte" refers to immersing or exposing a portion of the stainless steel to the electrolyte.

[0017] In the measurement method of this embodiment, the anodic polarization curve of stainless steel is measured. Here, the anodic polarization of stainless steel indicates that when the potential of stainless steel in contact with an electrolyte is swept (applied) in the positive direction, the stainless steel acts as an anode, and corrosion or the formation of an oxide film progresses. The anodic polarization curve is a curve plotting the current density (electrolysis flow rate density or charge amount) generated during anodic polarization against the applied potential.

[0018] In the measurement method of the present embodiment, the amount of charge (current or current density) caused by the dissolution of chromium carbide and / or chromium nitride into the electrolyte is measured from the above-mentioned anodic polarization curve.

[0019] Here, chromium carbide (Cr carbide) is, for example, Cr 23 C6, etc. Chromium nitrides (Cr nitrides) are, for example, CrN, Cr2N, etc.

[0020] When Cr carbide and / or Cr nitride precipitate in the stainless steel, a curve region originating from the Cr carbide and / or Cr nitride appears in the anodic polarization curve of the stainless steel. By reading the peaks and areas of these curve regions, the amount of charge corresponding to the Cr carbide and / or Cr nitride can be measured.

[0021] In the measurement method of this embodiment, the precipitation of Cr carbides and / or Cr nitrides that cause sensitization can be confirmed by measuring the charge amount of Cr carbides and / or Cr nitrides from the anodic polarization curve of stainless steel that has been brought into contact with an electrolytic solution having a pH of 15 to 16. Therefore, the corrosivity of stainless steel can be evaluated with high accuracy.

[0022] Furthermore, in the measurement method of the present embodiment, the charge amount of Cr carbide and / or Cr nitride can be measured at the work site (on-site) of welding, etc. Therefore, the corrosiveness can be easily evaluated.

[0023] Furthermore, in the measurement method of this embodiment, there is no need to collect samples for measurement, and an electrolyte with a pH of 15 to 16 dissolves only the Cr carbides and / or Cr nitrides precipitated in the stainless steel under anodic polarization, without dissolving the stainless steel (base material) itself, which prevents a decrease in the mechanical strength of the stainless steel.

[0024] In addition, since duplex stainless steel has a relatively high Cr content, Cr carbides and / or Cr nitrides tend to precipitate easily. In contrast, in the measurement method of the present embodiment, by measuring the charge of Cr carbides and / or Cr nitrides, when the stainless steel to be measured is duplex stainless steel, the corrosiveness of duplex stainless steel, which is prone to significant sensitization, can be evaluated with high accuracy.

[0025] Furthermore, in stainless steel welds, a passive film of Cr is formed by welding, but Cr carbides and / or Cr nitrides are also likely to form at the same time. In contrast, the measurement method of the present embodiment measures the charge of Cr carbides and / or Cr nitrides, and when part of the stainless steel to be measured is a stainless steel weld, the corrosivity of the stainless steel weld where sensitization becomes significant can be evaluated with high accuracy.

[0026] <Evaluation method> In the evaluation method of this embodiment, the amount of chromium carbide and / or chromium nitride precipitated in the stainless steel is evaluated based on the electrical quantity obtained by the above-mentioned measurement method.

[0027] The Cr carbide and / or Cr nitride dissolved in the electrolyte under anodic polarization can be regarded as the Cr carbide and / or Cr nitride precipitated in the stainless steel. Therefore, the amount of charge due to the dissolution of chromium carbide (Cr carbide) and / or chromium nitride (Cr nitride) in the electrolyte can be converted into the amount of Cr carbide and / or Cr nitride precipitated in the stainless steel.

[0028] In this embodiment, for example, a potentiostat is used to perform anodic polarization measurement and obtain a potential-current density curve (FIG. 1). The potential range is swept from the natural potential to about +0.5 V. At this time, oxygen is generated when the potential exceeds +0.5 V. The potential sweep rate is preferably 200 mV or less. If the potential exceeds 200 mV, a clear peak in the current value cannot be obtained.

[0029] One of the obtained peaks corresponds to the dissolution of Cr carbide (A in Fig. 1) and the other corresponds to the dissolution of Cr nitride (B in Fig. 1). The charge amount corresponding to the dissolution of Cr carbide and Cr nitride is calculated from the obtained potential-current density curve (B in Fig. 1).

[0030] In the evaluation method of the present embodiment, by evaluating the amount of precipitation of Cr carbides and / or Cr nitrides in stainless steel in this manner, the corrosiveness of stainless steel can be evaluated with even higher accuracy.

[0031] Furthermore, by using the evaluation method of this embodiment, it is possible to easily evaluate the amount of Cr carbides and / or Cr nitrides precipitated in stainless steel on-site (at a work site, etc.).

[0032] <Measurement equipment> 2 shows the measurement device according to this embodiment. The measurement device 1 includes an electrolytic cell 10, an opening 10A, a potentiostat 70, and a data recording device 80.

[0033] The electrolytic cell 10 contains an electrolytic solution 20. The electrolytic solution 20 is the above-mentioned electrolytic solution having a pH of 15 to 16. In this embodiment, a saturated aqueous solution of potassium hydroxide (KOH) adjusted to a pH of 15 to 16 is contained in the container 10. The electrolytic cell 10 is preferably made of a material that is resistant to an electrolytic solution having a pH of 15 to 16. In this embodiment, the electrolytic cell 10 is made of a container made of a resin such as polyethylene.

[0034] In the electrolytic cell 10, a target electrode 30 and a reference electrode 40 are disposed in a state immersed in the electrolytic solution 20. The target electrode 30 is also called a counter electrode, and constitutes an anode under anodic polarization. The material of the target electrode 30 is not particularly limited, and may be made of, for example, carbon (C). The reference electrode 40 is also called a reference electrode or standard electrode, and constitutes a cathode under anodic polarization. The material of the reference electrode 40 is not particularly limited, and may be made of, for example, silver / silver chloride (Ag / AgCl).

[0035] The opening 10A is formed in the electrolytic cell 10 to bring the electrolytic solution 20 into contact with the stainless steel M. In this embodiment, the stainless steel M has a base metal MP and a weld metal WP (weld portion), and the stainless steel M is fixed to the opening 10A so that the weld metal WP (weld portion) comes into contact with the electrolytic solution 20.

[0036] The opening 10A is further provided with a sealant 50. The sealant 50 seals the gap between the stainless steel M, which contacts the electrolytic solution 20, and the opening 10A. The form of the sealant 50 is not particularly limited, and for example, an O-ring, a gasket packing, or the like can be used. The material of the sealant 50 is preferably a material that is resistant to an electrolytic solution with a pH of 15 to 16. In this embodiment, the sealant 50 is an O-ring made of a rubber material such as silicone rubber.

[0037] The manner in which the stainless steel M is brought into contact with the electrolytic solution 20 is not particularly limited. For example, the electrolytic solution 20 is poured into an electrolytic cell (container) 10 placed with the opening 10A facing upward, and the stainless steel M is placed over the opening 10A from above and fixed in a sealed state with a sealant 50. Then, with the stainless steel M fixed in place, the electrolytic cell (container) 10 is turned upside down. Alternatively, the electrolytic solution 20 may be made into a gel and stored in the electrolytic cell (container) 10 in a state in which it is difficult to flow.

[0038] The electrolytic cell (container) 10, electrolyte 20, target electrode 30 and reference electrode 40 configured in this manner constitute a single electrochemical cell with the stainless steel M fixed to the opening 10A of the electrolytic cell (container) 10 (with the stainless steel M in contact with the electrolyte 20).

[0039] The potentiostat 70 measures the anodic polarization curve of the stainless steel M in contact with the electrolyte 20. In this embodiment, the potentiostat 70 is connected to the target electrode 30 and the reference electrode 40, and sweeps (applies) a potential to the stainless steel M under anodic polarization.

[0040] The potentiostat 70 is connected to a portion of the base material MP of the stainless steel M that does not contact the electrolytic solution 20 via a conductor 60 such as a copper wire. This allows the potentiostat 70 to detect the current generated in the stainless steel M under anodic polarization. The potentiostat 70 can create an anodic polarization curve (FIG. 1) of the stainless steel M from the current detected in this manner.

[0041] The data recording device 80 is connected to the potentiostat 70, and measures the amount of charge due to the dissolution of Cr carbide and / or Cr nitride into the electrolyte from the anodic polarization curve (FIG. 1) measured by the potentiostat 70. Specifically, similarly to the above-mentioned measurement method, the amount of charge corresponding to Cr carbide and / or Cr nitride is measured by reading the peaks and areas of the curve regions originating from Cr carbide and / or Cr nitride that appear in the anodic polarization curve.

[0042] The data recording device 80 can readably and rewritably store the anodic polarization curve (FIG. 1) measured by the potentiostat 70 and the amount of charge corresponding to the Cr carbide and / or Cr nitride measured by the data recording device 80.

[0043] The data recording device 80 may be provided with a control unit such as a CPU. The control unit controls, for example, the operation of measuring the anodic polarization curve by the potentiostat 70 and the operation of measuring the amount of charge of the chromium carbide and / or chromium nitride by the data recording device 80.

[0044] The data recording device 80 may be provided as an option, or the potentiostat 70 may be provided with the function of measuring the amount of charge corresponding to Cr carbide and / or Cr nitride without providing the data recording device 80.

[0045] The measuring device 1 of this embodiment substantially includes the configuration of the above-mentioned measuring method, and therefore has the same effects as the above-mentioned measuring method. Specifically, by measuring the charge amount of Cr carbide and / or Cr nitride from the anodic polarization curve of stainless steel M contacted with electrolytic solution 20 having a pH of 15 to 16, it is possible to confirm the precipitation of Cr carbide and / or Cr nitride, which cause sensitization. Therefore, the corrosivity of stainless steel M can be evaluated with high accuracy.

[0046] The measurement device 1 of the present embodiment can measure the charge amount of Cr carbide and / or Cr nitride at the work site (on-site) of welding, etc., and therefore, the corrosiveness can be easily evaluated.

[0047] Furthermore, in the measurement device 1 of this embodiment, there is no need to collect samples for measurement, and the electrolytic solution 20 having a pH of 15 to 16 dissolves only the Cr carbides and / or Cr nitrides precipitated in the stainless steel M under anodic polarization, without dissolving the base metal MP of the stainless steel M. Therefore, a decrease in the mechanical strength of the stainless steel M can be prevented.

[0048] Furthermore, as described above, the measuring device of this embodiment is provided with the sealing material 50 at the opening 10A of the electrolytic cell 10, thereby making it possible to seal the gap between the stainless steel M in contact with the electrolytic solution 20 and the opening. This allows the electrolytic cell (container) 10, the electrolytic solution 20, the target electrode 30, and the reference electrode 40 to constitute a single electrochemical cell with the stainless steel M in contact with the electrolytic solution 20, so that the anodic polarization curve of the stainless steel M can be measured with high accuracy. EXAMPLES

[0049] In the following, in this embodiment, a duplex stainless steel was used as the stainless steel M in FIG. 2, and an evaluation of Cr carbides and Cr nitrides in the duplex stainless steel was carried out for the welded portion WP of the duplex stainless steel.

[0050] The duplex stainless steel used was S32750.

[0051] The welded portion WP of the duplex stainless steel M was a welded joint fabricated by TIG welding using a welding rod (not shown) with approximately the same composition as the base metal. The surface of the welded joint fabricated was polished with #1000 emery paper.

[0052] An electrochemical cell (electrolytic cell 10, electrolyte 20, target electrode 30, reference electrode 40, sealing material 50, and duplex stainless steel M in Figure 2) was placed so that a part of the base metal MP of the duplex stainless steel M and the weld metal WP were in contact with a saturated potassium hydroxide aqueous solution (electrolyte 20).

[0053] Using a potentiostat 70, the potential was swept up to 0.3 mV at a potential sweep rate of 100 mV / min to obtain a potential-current density curve (FIG. 1).

[0054] Two current peaks were obtained between -0.1 and 0.1 mV. Observation of the structure using a scanning electron microscope (SEM) before and after the measurement revealed that the two current peaks corresponded to the dissolution of Cr carbide (A in Fig. 1) and Cr nitride (B in Fig. 1), respectively.

[0055] By calculating the charge of these peaks, it is possible to evaluate the amount of Cr carbide and Cr nitride precipitates.

[0056] The above disclosed embodiments include, for example, the following aspects.

[0057] (Appendix 1) The stainless steel is placed in contact with an electrolyte with a pH of 15 to 16. measuring an anodic polarization curve of the stainless steel; a measurement method for measuring an amount of charge resulting from dissolution of chromium carbide and / or chromium nitride into the electrolyte from the anodic polarization curve.

[0058] (Appendix 2) 2. The measurement method of claim 1, wherein the stainless steel is a duplex stainless steel.

[0059] (Appendix 3) 3. The measurement method of claim 1, wherein the portion of the stainless steel in contact with the electrolyte is a welded portion of the stainless steel.

[0060] (Appendix 4) 4. A method for evaluating the amount of chromium carbide and / or chromium nitride precipitates in the stainless steel based on the electrical quantity obtained by the measurement method according to any one of claims 1 to 3.

[0061] (Appendix 5) an electrolytic cell containing an electrolyte having a pH of 15 to 16; an opening formed in the electrolytic cell for allowing the electrolyte to contact a stainless steel; a potentiostat for measuring an anodic polarization curve of the stainless steel in contact with the electrolyte; a measuring device for measuring an amount of charge resulting from the dissolution of chromium carbide and / or chromium nitride into the electrolyte from the anodic polarization curve.

[0062] (Appendix 6) 6. The measurement device of claim 5, further comprising a sealant provided in the opening to seal between the stainless steel in contact with the electrolyte and the opening.

[0063] Although an embodiment of the present invention has been described above, the present invention is not limited to a specific embodiment, and various modifications and changes are possible within the scope of the invention described in the claims. [Explanation of symbols]

[0064] 1. Measurement equipment 10 Electrolytic cell (container) 10A aperture 20 Electrolyte 30 Target Electrode 40 Reference electrode 50 Sealing material (O-ring) 60 Conductor wire (copper wire) 70 Potentiostat 80 Data Recording Device

Claims

1. Contacting the stainless steel with an electrolyte having a pH of 15-16; measuring an anodic polarization curve of the stainless steel; a measurement method for measuring an amount of charge resulting from dissolution of chromium carbide and / or chromium nitride into the electrolyte from the anodic polarization curve.

2. The method of claim 1 , wherein the stainless steel is a duplex stainless steel.

3. The measurement method according to claim 1 , wherein the portion of the stainless steel that contacts the electrolyte is a welded portion of the stainless steel.

4. 4. A method for evaluating an amount of chromium carbide and / or chromium nitride precipitates in the stainless steel based on an electrical quantity obtained by the measurement method according to claim 1.

5. an electrolytic cell containing an electrolyte having a pH of 15 to 16; an opening formed in the electrolytic cell for allowing the electrolyte to contact a stainless steel; a potentiostat for measuring an anodic polarization curve of the stainless steel in contact with the electrolyte; a measuring device for measuring an amount of charge resulting from the dissolution of chromium carbide and / or chromium nitride into the electrolyte from the anodic polarization curve.

6. The measuring device according to claim 5 , further comprising a sealant provided in the opening to seal between the stainless steel in contact with the electrolyte and the opening.

Citation Information

Patent Citations

  • Epoxy resin composition for sealing semiconductor element, and semiconductor device sealed using the same

    JP2021178953A

  • Epoxy resin composition for semiconductor device encapsulating film, semiconductor device encapsulating film and semiconductor device encapsulated using the same

    JP2021181559A